Renée Hirschon (ed.), 2003, Crossing the Aegean. An Appraisal of the 1923 Compulsory Population Exchange between Greece and Turkey. Studies in Forced Migration, Volume 12, Oxford, New York, Berghahn Books, pp xix+298 - Petronoti, Marina (The Greek Review of Social Research, 2004)
Δε διατίθεται περίληψη / no abstract available